Construction and Application of Dynamic Evaluation System and Educational Model of College Students' Mental Health - Yaling Li (Frontiers Media S.A., 2022)
The aim of the paper is a dynamic evaluation system that provides support to the students' mental health. Mental health contains students' feelings, psychological, and social well-being. Extracurricular activities, professional and innovative skills, self-awareness, emotional management, cultural norms, and personality development are the essential factors in a dynamic evaluation system for students' mental health. Extracurricular activities support learning additional things except for the subjects. Thinking skill is being an optimistic idea to mental health. Through professional and innovative skills, students can express their thoughts and ideas with others. Understanding one's feelings are considered self-awareness. It supports finding the good and uniqueness of a particular person. Emotional management accepts and controls the feelings of the students. Virtue, ethics, honesty, loyalty, responsibility, positive thoughts, relational skills are the important factors in cultural norms. Feelings and ways of behavior affect mental health in personality development. Self-confidence is the main element in personality development. This article engaged to adopt a descriptive research method to present a perfect model for this research. The probability method (random sampling method) and non-probability method (purposive sampling method) were utilized for this research. A total of 349 sample sizes of college students participated in the questionnaire survey and 12 sample sizes of college instructors responded to the face-to-face interview from the priority areas of the university. Finally, Thus, in this research, extracurricular activities and professional and innovative skills are dominant factors when examining other factors. These leading factors are expressed clearly by students to protect their mental health of the students.